PENGARUH NYALA API PADA LAS OXY-ACETYLENE TERHADAP KEKUATAN IMPAK PADA PROSES BRAZING BAJA KARBON RENDAH - Muhammad Naufal; Tuparjono Tuparjono; Rodika Rodika (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Brazing is a method of joining metal materials through a heating process using an adhesive or filler that has a lower melting point than the melting point of the material to be joined. Oxy-acetelyne welding is a manual welding process where the metal surface to be joined is heated until it melts by an acetylene gas flame through the combustion of C2H2 and O2 with or without filler metal where the joining process is without pressure. In this study using an experimental method. The purpose of this study was to determine the impact strength of low carbon steel after the brazing process with variations in flame and root gap. The variations of the flame used are oxidation flame, neutral flame and carburizing flame with a root gap of 0.4mm, 0.6mm, and 0.8mm. The material used in this research is mild steel St37. The added material used is 3mm diameter brass wire. From the research that has been carried out, it shows that the energy absorbed and the impact value on welding after calculation with the highest value on a neutral flame with a Root gap of 0.8 and the lowest value on a carburizing flame with a Root gap of 0.4.